The importance of the pharmaceutical professional in the quality of life of elderly diabetic patients (Research, Society and Development, 2020)
Diabetes Mellitus (DM) is characterized by an increase in the concentration of glucose in the bloodstream due to insulin deficiency. There are two types of Diabetes Mellitus, in type 1 DM, when the individual's pancreas produces little or no insulin, requiring daily insulin injections. Only 10% of diabetics have DM1, manifesting mainly in children and adolescents. Type 2 DM also appears in children and young people, but is more common after the age of 40, in overweight and elderly people, in this situation the pancreas continues to produce insulin, but the body becomes resistant to its effects. For therapeutic intervention in diabetic patients, it is important to highlight that non-drug and drug treatment should be used. Drug treatment can be done through the use of insulin and / or oral antidiabetics (ADOs) to establish glycemic control and promote a decrease in glycated hemoglobin levels. Given the importance of the theme, the present study aimed to investigate the incidence of elderly patients with Diabetes Mellitus in an elderly shelter, as well as the type of drug treatment used. For this procedure, an exploratory, descriptive and retrospective study was carried out, with a qualitative and quantitative approach, by collecting data from the information bank of an elderly shelter in Teresina-PI, in September 2019. More men were found, with the predominant age group of 70 years and a 13% incidence of diabetics, with equal numbers of men and women. In this universe of diabetics, glibenclamide (oral antidiabetic) predominantly led the use, without the existence of any insulin dependent patient. Thus, we can conclude that the important research showed a low incidence of diabetics in this researched shelter, however the relationship between Diabetes and the elderly is a reality that requires the intercession of a prepared multiprofessional team. It is worth highlighting the importance of the pharmaceutical professional working directly with Family Health Care, thus providing a better treatment and consequently better quality of life for the elderly patient.